Water diplomacy: an important tool for climate change mitigation and sustainable development - José Noronha Rodrigues; Sumanta Bhattacharya; Dora Cristina Ribeiro Cabete; Ardyllis Alves Soares (Revista de Direito Econômico e Socioambiental)
A key instrument for combating climate change, preserving the environment and promoting sustainable development is water diplomacy. For this reason, in this article, the authors look at the various aspects of water diplomacy, including international collaboration, cross-border water protection, data exchange, ecological protection, flood management and global food security. Given that water transcends borders, the authors address various agreements concluded between countries to manage rivers, lakes and basins of groundwater common to several nations, requiring international cooperation and diplomacy that are of particular value to this study. Water diplomacy promotes comprehensive conversations and solutions. Diplomacy is used to bring together stakeholders to create comprehensive water resource management plans. This article employs a descriptive, interpretative, qualitative-quantitative methodology based on the use of primary sources, international and national instruments, as well as the conduct of documentary and bibliographic research. The results obtained allow the authors to conclude that it is impossible to underestimate the importance of water diplomacy for international relations and society. Water diplomacy promotes social justice by putting the needs of all parties first, including historically marginalized groups. Water diplomacy can prevent social inequality in water management and allocation by using inclusive decision-making procedures increasing social equity.